Protagonismo juvenil e capital humano: uma análise da participação política da juventude no Brasil - Marcos Vinicius da Silva Goulart; Nair Iracema Silveira dos Santos (Ciências Sociais Unisinos)
This article analyzes, from the perspective of social psychology, the political and social participation of youth. The year 1985 was declared “International Year of Youth” by the United Nations (UN), and in that connection the political role of young people for social development was highlighted not only in developing countries, but in developed countries as well. In this context, inspired by Foucault’s genealogical frame of reference, we analyze how the relation between youth, social development, and political participation appears in the field of interests of international cooperation agencies and nongovernmental organizations. Youth protagonism and volunteerism served as analyzers of this process, in which we intend to demonstrate that both are directly related, prescribing young people ways of being and acting. The notion of human capital is used, allowing us to indicate that the political and social action of youth can be seen as a kind of investment in themselves and a mode of subjectivation.